Tribute to Watt Taylor - Kantor, Mark (Journal of Affordable Housing & Community Development Law)
Watt was always happy to provide advice and guidance to all who had questions for him on HUD and Fair Housing issues, and particularly enjoyed providing younger attorneys with advice and information. Whether celebrating a birthday, an achievement in school, or Mason on the football field, he always had a sparkle in his eye and a bounce in his step. Watt loved to travel-to Europe, the South Pacific, India, and most dear to his heart Uganda.